2019
DOI: 10.4067/s0034-98872019000500618
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness y la relación clínica: pasos hacia una resiliencia en medicina

Abstract: Mindfulness and the clinical relationship: steps to a resilience in medicine Medical resilience is a dynamic capacity, which has the potential to improve the well-being of physicians and to enhance the quality of the clinical relationship. Strategies to promote resilience are important to achieve a sustainable medical practice and improve patient care. Mindfulness training has demonstrated to be an effective tool to promote resilience in physicians. This paper contextualizes the place of mindfulness in medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, in the specific case of mindfulness practice, it has been proven to be an efficient tool to promote resilience among physicians [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the specific case of mindfulness practice, it has been proven to be an efficient tool to promote resilience among physicians [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors claim that it can be a means of empathetically and intuitively connecting with the patient's inner world through identification and projective identification (Athanasiadou & Halewood, 2011). Hilari (2017) claims that it promotes self‐regulation, which is related to stress management and self‐regulation of the therapist during therapy, which helps them to take premeditated decisions and prevents them from falling into a state of automatic functioning that often occurs in the clinic, thereby reducing the risk of making mistakes in clinical practice (Krogh et al., 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…35 Positive affect was strongly associated with resilience in physicians, 36 and previous evidence has suggested that levels may determine the likelihood of a lack of resilience in resulting in burnout. 37 Theoretical links have been made between mindfulness and resilience, 38 and dispositional mindfulness scores have been shown to be associated with higher resilience in healthcare professionals. 39,40 Strong coping skills have been associated with resilience in patients.…”
Section: Psychological Variables Associated With Resilience: Adaptive...mentioning
confidence: 99%